2011
DOI: 10.1158/1541-7786.mcr-11-0090
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of HIF and USF Signaling Pathways in Human Genes Flanked by Hypoxia-Response Elements and E-box Palindromes

Abstract: Rampant activity of the hypoxia-inducible factor (HIF)-1 in cancer is frequently associated with the malignant progression into a harder-to-treat, increasingly aggressive phenotype. Clearly, anti-HIF strategies in cancer cells are of considerable clinical interest. One way to fine-tune, or inhibit, HIF's transcriptional outflow independently of hydroxylase activities could be through competing transcription factors. A CACGTG-binding activity in human hepatoma cells was previously found to restrict HIF's access… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 67 publications
3
11
0
Order By: Relevance
“…Conversely, reduction of USF2 expression by siRNA increased hypoxic activation of some HIF1 target genes, such as KCTD11, BNIP3L, and GRP111, in hypoxic Hep3B cells (Table 1). This inhibitory role of USF2 for some HIF1 target genes is consistent with previous reports indicating that HREs of some HIF1 target genes, such as LDHA, BNIP3, and LPK, are bound by USF1/USF2 under normoxia or in response to glucose activation but by HIF1 in hypoxic cells (49,62). However, while the previous reports indicated that USF1/USF2 and HIF1 compete for the same binding site on some HIF1 target promoters during hypoxia, we show that USF2 and HIF2 bind to different sites of HIF2 target genes in an uncompetitive manner in vitro (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, reduction of USF2 expression by siRNA increased hypoxic activation of some HIF1 target genes, such as KCTD11, BNIP3L, and GRP111, in hypoxic Hep3B cells (Table 1). This inhibitory role of USF2 for some HIF1 target genes is consistent with previous reports indicating that HREs of some HIF1 target genes, such as LDHA, BNIP3, and LPK, are bound by USF1/USF2 under normoxia or in response to glucose activation but by HIF1 in hypoxic cells (49,62). However, while the previous reports indicated that USF1/USF2 and HIF1 compete for the same binding site on some HIF1 target promoters during hypoxia, we show that USF2 and HIF2 bind to different sites of HIF2 target genes in an uncompetitive manner in vitro (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…1D, P < 0.05 vs HIF1α only). This inhibitory role of USF2 for some HIF1 target genes is consistent with previous reports indicating that HBSs of some HIF1 target genes, such as LDHA , BNIP3 , and LPK , are bound by USF1/USF2 under normoxia but by HIF1 in hypoxic cells [34] as we also observed previously [29]. The weak activation of HIF1 target gene reporters by HIF2 was not changed by co-transfection of STAT3 or USF2 (Fig.…”
Section: Resultssupporting
confidence: 92%
“…9A). This could not be explained by USF2’s role in binding to HBS and activating HIF1 target genes under normoxia [43] as RCC4 cells exhibit constitutive HIF activity.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is a major feature of solid tumors and induces hypoxia-inducible factor-1α (HIF-1α) which binds to the hypoxia-response elements (HREs) of various target genes and activates their transcription to regulate glucose transport and angiogenesis, and potentially enhance the survival of tumor cells (1822). Our previous studies have shown that hypoxia modulates the downregulation of CDX2 in colorectal cancer (23).…”
Section: Introductionmentioning
confidence: 99%